Bisphosphonates and Osteonecrosis of the Jaw: A Multidisciplinary Approach - De Ponte, Francesco Saverio; SpringerLink (Online service) (Milano : Springer Milan, 2012)
Bisphosphonates are commonly prescribed to inhibit bone loss in patients with osteoporosis, as well as osteopenia, cancer, and Paget's disease of the bone. Recently, scientific literature has addressed a possible relationship between bisphosphonates and osteonecrosis of the jaw (ONJ). It is important to note that though the risks for developing ONJ are much higher for cancer patients on intravenous bisphosphonate therapy (used to reduce bone pain), the occurrence of ONJ also in patients treated with oral BF for osteoporosis has been also highlighted, though rarely. On the basis of the large use of BF, of their pharmacokinetics, of the systemic and local risk factors, physicians prescribing them and dental surgeons should be well informed on the various aspects of the problem. Aim of this volume is to offer an update on the current status of prevention, and on the current conservative and surgical treatments. The multidisciplinary approach will be very much appreciated by GP$1 (Bs, the different specialists using bisphosphonates and by dental surgeons.s
Keywords: Medicine; Dentistry; Pharmacy; Family medicine; Radiology, Medical; Hematology; Surgery; Medicine & Public Health; Oral and Maxillofacial Surgery; Dentistry; Hematology; General Practice / Family Medicine; Pharmacy; Imaging / Radiology